Passive Infrared Sensing Using Plasmonic Resonant Dust Particles - Mark Mirotznik; William Beck; Kimberly Olver; John Little; Peter Pa (International Journal of Optics)
We present computational and experimental results of dust particles that can be tuned to preferentially reflect or emit IR radiation within the 8–14 μm band. The particles consist of thin metallic subwavelength gratings patterned on the surface of a simple quarter wavelength cavity. This design creates distinct IR absorption resonances by combining the plasmonic resonance of the grating with the natural resonance of the cavity. We show that the resonance peaks are easily tuned by varying either the geometry of the grating or the thickness of the cavity. Here, we present a computational design algorithm along with experimental results that validate the design methodology.